Empowerment of Coastal Communities through Utilization of Fish Waste in Realizing a Blue Economy - Musoffan, Musoffan; Sholeh, Mohammad Shoimus; Suprapto, Helman (Jurnal Abdimas, 2023)
Fish waste, which includes fish innards, fish heads and bones, as well as remaining fish washing water, if not managed properly, can cause environmental pollution. This waste is increasing day by day. This will have a deadly impact on biota invertebrates Which No with other shells, therefore it is necessary to process fish waste so that it can at least reduce environmental pollution. To control efforts , a service activity program is needed, namely socialization and training on the Implementation of the Blue Economy by Utilizing Fish Waste into Catfish and Petis Feed in Tlesah Village, Tlanakan District, Pamekasan . By holding this training, the community understands how to use fish waste into products that have economic value and understand the stages of making products starting from preparing tools and materials, the length of the production process until it becomes fish food and paste products. Partners' knowledge about the blue economy has increased after the presentation of the material by viewing response to material conclusions empowerment after a demonstration or practice of utilizing fish waste.